Some Notes on the Tragic Writing of Antonio Gramsci - Almeida Rodriguez, Manuel S. (International Gramsci Journal, 2023)
This essay considers the tragic elements present in Gramsci’s prison writings, including both the Prison Notebooks and the Prison Letters. It highlights specific moments in both the notebooks and the letters in which this tragic element presents itself. These include the interpretation of the often cited motto of ‘pessimism of the intellect, optimism of the will’ present in the notebooks, of the für ewig character of the notebooks as expressed in an important prison letter, and of other important passages. Also, it shows how the tragic element expresses at the same time the fusion of Gramsci’s personal tragedy with the political tragedy of the Left in general. Finally, the essay treats on how this tragic element transcends itself in the claim for the fertilizing of the social terrain for a better future.